SOCIAL VALUES IN THE MAIN CHARACTER OF THE NOVEL DILAN: DIA ADALAH DILANKU TAHUN 1991 BY PIDI BAIQ: A SOCIOLOGY OF LITERATURE STUDY - Arita Gustianti; Sulthaanika Ferdy Syahwardi; Zahroh Nurhillal; Elda Yulian Agustine (RADJA PUBLIKA, 2025)
This study discusses social values ​​in the novel Dilan (Dia adalah Dilanku Tahun 1991) by Pidi Baiq through a sociology of literature approach. This study aims to reveal the social values ​​reflected in the main characters of the novel Dilan: Dia adalah Dilanku Tahun 1991 by Pidi Baiq through a sociology of literature approach. This novel describes the dynamics of adolescent relationships that are full of inner conflict, affection, and social interaction in society. The character Dilan shows social values ​​such as caring, empathy, loyalty, responsibility, and tolerance, which are conveyed through a light, humorous, and distinctive writing style. The study uses a qualitative descriptive method with reading and note-taking techniques and the Miles and Huberman interactive analysis model. The results of the study show that the social values ​​in this novel not only reflect the character of the character, but also represent the reality of adolescent life in urban society in the 1990s. This novel is an effective medium for reflecting social norms and shaping the moral attitudes of the younger generation.